2013
DOI: 10.15288/jsad.2013.74.626
|View full text |Cite
|
Sign up to set email alerts
|

Smokers Report Greater Demand for Alcohol on a Behavioral Economic Purchase Task

Abstract: ABSTRACT. Objective: Cigarette smokers have higher levels of alcohol consumption than nonsmokers and poorer response to alcohol treatment. It is possible that the greater severity of alcohol problems observed in smokers refl ects a greater susceptibility to alcohol-related reinforcement. The present study used a behavioral economic purchase task to investigate whether heavy drinking smokers would have greater demand for alcohol than heavy drinking nonsmokers. Method: Participants were 207 college students who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 59 publications
5
34
2
Order By: Relevance
“…More specifically the purchases of high-grade marijuana made by our sample of frequent, (almost daily) relatively heavy (about 3 joints/episode) marijuana users generated demand curves and indices of relative reinforcement efficacy (RRE) that matched those generated in similar laboratory tasks involving tobacco (MacKillop et al, 2008) and alcohol (Murphy, MacKillop, Skidmore & Pederson, 2009; Yurasek et a., 2013). The participants were willing to purchase marijuana until the price reached a breakpoint of $38.07 per joint, suggesting that marijuana is highly reinforcing.…”
Section: Discussionmentioning
confidence: 91%
“…More specifically the purchases of high-grade marijuana made by our sample of frequent, (almost daily) relatively heavy (about 3 joints/episode) marijuana users generated demand curves and indices of relative reinforcement efficacy (RRE) that matched those generated in similar laboratory tasks involving tobacco (MacKillop et al, 2008) and alcohol (Murphy, MacKillop, Skidmore & Pederson, 2009; Yurasek et a., 2013). The participants were willing to purchase marijuana until the price reached a breakpoint of $38.07 per joint, suggesting that marijuana is highly reinforcing.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies examining alcohol demand have also found different relationships between predictor variables and alcohol demand intensity and other demand indices. For example, Yurasek and colleagues 47 found that as compared to heavy drinking nonsmokers, heavy drinking smokers had significantly higher O max , P max , and breakpoint but not higher intensity.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the negative reinforcing properties of alcohol may be particularly salient for those experiencing aversive psychological symptoms. Another interesting recent study of college drinkers identified alcohol demand to be higher in smokers even after controlling for alcohol consumption, gender, alcohol problems, and depressive symptoms [22]. These latest studies suggest that alcohol demand uniquely contributes to the relationship between elevated alcohol use and co-occurring processes such as negative affective symptoms and cigarette smoking.…”
Section: Alcohol Demandmentioning
confidence: 99%